Estimation and comparative evaluation of teeth prominence values of Saudis for bracket prescription - Ferdous Bukhary; Mohammed T. Bukhary; Fares Alhabbad; Sahar Albarakati (Elsevier, 2021)
Background: The racial and ethnic disparities in tooth morphology and alignment indicate the need for different orthodontic prescriptions. Purpose: This study aimed at utilizing the 3D digital models to measure the teeth prominence of Saudi adults and compare the results to previously published data. Materials and methods: The sample included 60 sets of 3D digital dental models of subjects who presented with non-orthodontic normal occlusion and balanced profile. Rhinoceros™ 3D modeling software was used to mark the midpoint of the clinical crown (LA) and the embrasure line and then to measure the prominence of the teeth. The collected data was analyzed using SPSS (IBM SPSS Inc., version 20, Chicago, IL, USA). The mean and SD scores were obtained for each measurement. Independent t-test, paired t-test, and student t-test were used for the comparison at a significant level of P ≤ 0.05. Result: Comparison between the right and the left sides, and between the male and female showed no significant differences, and hence the result data were combined. However, further comparison with the published data of the North American whites, Japanese, Indian, African and Italian showed significant differences in most of the teeth. Conclusion: Racial differences influence the teeth prominence values that should be considered in presenting orthodontic bracket prescriptions. More research in this field is needed.